The rising trend of becoming a geography teacher as a catalyst for sustainable development goals implementation in schools - Utami, Dian; Angelita, Ika (Journal of Environment and Geography Education, 2025)
Background: This study aims to investigate and analyze the level of student interest in pursuing a teaching career among those enrolled in the Geography Education Program at the Faculty of Teacher Training and Education, University of Lampung. Methods: The study population includes all students within the program, with the sample consisting of 69 students from the 2020 cohort. Of these, 58 active students participated in the survey. Data were collected through a structured questionnaire, which was subsequently tested for validity and reliability. This research adopts a single-variable approach encompassing three key indicators: cognitive, emotional (affective), and conative aspects. A descriptive quantitative method was employed, utilizing a purposive sampling technique. Data collection instruments included questionnaires and documentation, while data analysis was conducted using descriptive statistical methods. Findings: The findings indicate that student interest in becoming teachers is generally low, with 81.03% of responses across all three dimensions reflecting limited interest. This finding suggests a potential gap in future environmental education delivery in schools, as geography teachers play a vital role in integrating sustainability and environmental issues into classroom learning. Conclusion: These results raise concerns about the future of education, particularly in relation to the promotion and integration of Sustainable Development Goals (SDGs), including environmental education. Novelty/originality of this article: The declining interest in becoming geography teachers may hinder efforts to instill environmental awareness and the importance of nature conservation among younger generations through formal education.